Human Security dan Pelanggaran HAM: Studi Kasus Migrasi Warga Negara Ethiopia di Perbatasan Arab Saudi-Yaman 2022-2023 - Firdha Usmina Safitri; Agussalim Burhanuddin (Birokrasi: JURNAL ILMU HUKUM DAN TATA NEGARA, 2024)
Migration has been a significant social phenomenon since ancient times, evidenced by ancient humans migrating from Africa to other continents. Today, Ethiopia faces increased international emigration due to various conflicts, prompting many to seek better opportunities in Saudi Arabia. However, this migration process often entails serious risks to individuals' security and well-being, particularly concerning human rights violations. This paper examines these issues through the lens of human security, emphasizing the protection of migrants' physical safety, freedom from violence and exploitation, access to basic needs, and the preservation of human dignity.